APPLICATION OF SWOT ANALYSIS IN CONSTRUCTION INDUSTRY-A QUALITATIVE STUDY IN COIMBATORE DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The SWOT analysis technique can be used by an individual or organisation as part of their sustainable strategic approach in assessing their strengths, weaknesses, opportunities, and threats in connection to project planning and market rivalry. Although the method is still frequently utilized, it needs to be improved in order to be more useful in strategic management. This method, which involves "peeling back layers of the corporation," is intended to be utilized in the starting phases of the procedures to be followed in deciding the decisions and also be served as an effective device for assessing the long-term business position of critical zones of the various organizations (for-profit organization, regional and central governmental executive bodies, construction, etc.). Its purpose is to outline the project or business venture's objectives and describe both the internal and external elements which are advantageous and detrimental to accomplishing their goals. Making the TOWS or SWOT evaluation for the construction sector is the primary goal of this study in order to provide a thorough grasp of its internal and external factors. In order to accomplish their objectives along with goals, which will aid in the development of the construction sector, this article assists in studying the structure of the organisation additionally helps in determining the assessment of SWOT. The implementations of new technologies and tight quality control have significantly enhanced the construction process in comparison to the past. By adopting SWOT analysis, the firm may continuously progress in their industry. SWOT analyses and assesses both internal and external factors that have an impact on the operation and growth of the firm. The construction industry's SWOT analysis will enable stakeholders to comprehend the state of the market and the numerous opportunities that are now open to them.